The identification and differential expression of Eucalyptus grandis pathogenesis-related genes in response to salicylic acid and methyl jasmonate - Naidoo, Ronishree; Ferreira, Linda; Berger, Dave K.; Myburg, Alexander A.; Naidoo, Sanushka (Frontiers in Plant Science, 2013)
Two important role players in plant defence response are the phytohormones salicylic acid (SA) and jasmonic acid (JA); both of which have been well described in model species such as Arabidopsis thaliana. Several pathogenesis related (PR) genes have previously been used as indicators of the onset of SA and JA signalling in Arabidopsis. This information is lacking in tree genera such as Eucalyptus. The aim of this study was to characterise the transcriptional response of PR genes (EgrPR2, EgrPR3, EgrPR4, EgrPR-5 and EgrLOX) identified in Eucalyptus grandis to SA and methyl jasmonate (MeJA) treatment as well as to qualify them as diagnostic for the two signalling pathways. Using the genome sequence of E. grandis, we identified candidate Eucalyptus orthologs EgrPR2, EgrPR3, EgrPR4, EgrPR5 and EgrLOX based on a co-phylogenetic approach. The expression of these genes was investigated after various doses of SA and MeJA (a derivative of JA) treatment as well as at various time points. The transcript levels of EgrPR2 were decreased in response to high concentrations of MeJA whereas the expression of EgrPR3 and EgrLOX declined as the concentrations of SA treatment increased, suggesting an antagonistic relationship between SA and MeJA. Our results support EgrPR2 as potentially diagnostic for SA and EgrPR3, EgrPR4 and EgrLOX as indicators of MeJA signalling. To further validate the diagnostic potential of the PR genes we challenged E. grandis clones with the fungal necrotrophic pathogen Chrysoporthe austroafricana. The tolerant clone showed high induction of EgrPR2 and decreased transcript abundance of EgrPR4. Pre-treatment of the susceptible genotype with 5mM SA resulted in lesion lengths comparable to the tolerant genotype after artificial inoculation with C. austroafricana. Thus expression profiling of EgrPR2 and EgrPR4 genes could serve as a useful diagnostic approach to determine which of the two signalling pathways are activated against various pathogens in Eucalyptus.